Psychological perspectives on pathways linking socioeconomic status and physical health. [article]. - Matthews, Karen A
Low socioeconomic status (SES) is a reliable correlate of poor physical health. Rather than treat SES as a covariate, health psychology has increasingly focused on the psychobiological pathways that inform understanding why SES is related to physical health. This review assesses the status of research that has examined stress and its associated distress, and social and personal resources pathways related to SES that can serve as intermediate outcomes in future studies.-(from the authors)